The geomagnetic and geoelectric response to the May 2024 geomagnetic storm in the United Kingdom - Lawrence, E.; Beggan, C. D.; Richardson, G. S.; Reay, S.; Thompson, V.; Clarke, E.; Orr, L.; Hübert, J.; Smedley, A. R. D (Frontiers in Astronomy and Space Sciences, 2025)
The “Gannon” geomagnetic storm of 10 −12 May 2024 was the first extreme storm of the solar cycle 25 and the largest storm in more than 20years. The auroral electrojet, driven by a strong negative interplanetary magnetic field exceeding −50nT, moved towards the equator in the evening of the 10th May reaching the latitudes of central and southern England (below 54N) for several hours. Widespread sightings of the aurora were observed across the country, and rapid variations of the magnetic field were recorded in the United ingdom (UK). Here we present the geomagnetic and geoelectric data recorded during the storm in the UK together with models of ground effects and images of auroral displays around the country. We compare the May 2024 storm with geomagnetic data from the September 2017, October 2003, March 1989 as well as September 1859 Carrington event to demonstrate the differences in magnitude, timings and latitudinal extent between these events. We use the geomagnetic observations, and a ground electric field model based on magnetotelluric data combined with the high-voltage power grid network information to estimate geomagnetically induced currents (GICs) at substation level during the storm. The highest modelled GICs exceeded 60 A in substations in southwest and east−central England as well as northern Wales. Substation GICs modelled in higher latitude stations in Scotland exhibited lower values because the leading edge of the auroral oval rapidly moved to lower latitudes. The “Gannon” storm compared to historical storms on a global scale in terms of the aa* index, ranks third since 1868, after March 1989 and September 1941. However locally, the maximum magnetic field rate of change suggests it is closer to a 1−in−30 years event. Hence, there was relatively little impact on grounded technology in the United Kingdom.